(untitled) (Revista de Estudos da Linguagem, 1995)
This paper proposes a model ofreading processing based mainly on Fodor’s (1983) theory ofthe modularity ofthe mind. According to this model there are many domains ofprocessing in reading. Some ofthem are part of the linguistic module and others are part ofthe cognitive processor. Among the domains of the linguistic module there are lexical access and sintactic parsing. To build up the propositional scheme of a text and to integrate the propositional macrostructure of the text to the reader’s previous knowledge are tasks ofthe cognitive processor. This model also proposes aninterface between the linguistic module and the cognitive processor, where semantic parsing takes place.